China's economic zones : design, implementation and impact - Tao, Yitao, 1958-; Lu, Zhiguo (Economic history in China series., 2012)
"A thorough examination of the establishment and development of China's Special Economic Zones (SEZ). These eight SEZs marked a major milestone in China's gradual market-oriented reform process, and the developmental fluctuations of these zones offers an in-depth understanding of the complexities and difficulties of reform. They also provide critical insight into China's thirty years of economic and social transformation. This book is a valuable and practical resource for governments, academics and policy advisors looking for an insight into and analysis of how the Special Economic Zone strategy played a key role in the transformation of China's economy"--Provided by publisher.